Pengaruh Beban Kerja dan Lingkungan Kerja Non Fisik terhadap Kinerja Karyawan pada PT. Cesco Logistik Indonesia di Jakarta - Sunardi, Didi; Utami, Anisa Amelia Putri (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In today’s competitive business environment, employee performance is crucial for organizational success, especially in logistics companies where workload and work conditions greatly impact productivity. This study aims to examine the positive and significant influence of workload and the non-physical work environment on employee performance at PT. Cesco Logistik Indonesia in Jakarta. Using a quantitative associative approach, the research was conducted with 53 employees as respondents, selected through a census sampling method. Data were collected via a closed-ended questionnaire with a five-point Likert scale. Analysis was performed using multiple linear regression with SPSS 25, including descriptive analysis, validity and reliability tests, classical assumption tests, and regression analysis. The results indicate that both workload and the non-physical work environment individually and simultaneously have a positive and significant effect on employee performance. These findings suggest that managing workload proportionally and fostering a supportive psychological work environment can optimize employee performance. Consequently, these factors contribute to increased productivity, effectiveness, and motivation, positively influencing the overall achievement of organizational goals.